2018
DOI: 10.1097/j.pain.0000000000001174
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of naldemedine in the treatment of opioid-induced constipation in patients with chronic noncancer pain: a randomized, double-blind, placebo-controlled phase 3 study

Abstract: Supplemental Digital Content is Available in the Text.Naldemedine treatment of opioid-induced constipation was well tolerated for 52 weeks, did not precipitate opioid withdrawal, and increased bowel movements and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 32 publications
1
94
0
2
Order By: Relevance
“…Data to support naldemedine use come from 4 randomized double-blind trials comparing naldemedine against placebo including 1 phase 2b trial (Webster et al 46 ) and 3 phase 3 trials (COMPOSE 1, 2, and 3 47,48 ), including >2400 patients in total. The primary end point for 3 of these studies (Webster et al and COMPOSE 1 and 2 trials) was the ability to achieve at least 3 spontaneous bowel movements (SBM) per week.…”
Section: Peripherally Acting M-opioid Receptor Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data to support naldemedine use come from 4 randomized double-blind trials comparing naldemedine against placebo including 1 phase 2b trial (Webster et al 46 ) and 3 phase 3 trials (COMPOSE 1, 2, and 3 47,48 ), including >2400 patients in total. The primary end point for 3 of these studies (Webster et al and COMPOSE 1 and 2 trials) was the ability to achieve at least 3 spontaneous bowel movements (SBM) per week.…”
Section: Peripherally Acting M-opioid Receptor Antagonistsmentioning
confidence: 99%
“…Naldemedine is also the only prescription agent evaluated in this guideline, for which long-term (52-week) safety data are available. 48 The overall quality of evidence supporting use of naldemedine for management of OIC was considered high. The AGA issued a strong recommendation for use of naldemedine vs no treatment in patients with OIC refractory to laxatives.…”
Section: Peripherally Acting M-opioid Receptor Antagonistsmentioning
confidence: 99%
“…A new oral PAMORA, naldemedine, which has also demonstrated good efficacy and tolerability in a large clinical trial program [33][34][35], has recently been approved by the FDA and is currently undergoing licensing application at the EMA.…”
Section: Secretagoguesmentioning
confidence: 99%
“…[14][15][16] Additionally, 0.2 mg naldemedine is the approved therapeutic dose in the United States. The renal and hepatic impairment studies were designed in accordance with US FDA Guidance for Industry (Pharmacokinetics in Patients With Impaired Renal Function and Pharmacokinetics in Patients With Impaired Hepatic Function, respectively) as described below.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 A 0.2-mg dose of naldemedine was selected for these studies based on results from prior phase 2 and phase 3 studies, which demonstrated that 0.2 mg naldemedine administered once daily was a well-tolerated dose with efficacy for the treatment of opioid-induced constipation. [14][15][16] Additionally, 0.2 mg naldemedine is the approved therapeutic dose in the United States. 8 The renal impairment study consisted of 5 cohorts categorized as healthy subjects with normal renal function and subjects with mild renal impairment, moderate renal impairment, severe renal impairment, or end-stage renal disease (ESRD) requiring hemodialysis.…”
Section: Methodsmentioning
confidence: 99%